THE ANALYSIS OF REGIONAL CLUSTER DEVELOPMENT IN EUROPE AND CROATIA - Alka Obadic; Natasa Kurnoga Zivadinovic (European Regional Science Association (ERSA), 2011)
This paper investigates the main characteristics of regional clusters in EU 27 and Croatia. The special interest is focused on the economic performance of regional clusters in the Croatian economy. The main research question is: what characterises regional clusters in EU 27 and Croatia, and what are the main tendencies in cluster development? The cluster survey in this paper is focused on (i) the size and nature of the cluster, (ii) and which industrial activities in the clusters are performed. The purpose of this research is to analyse the importance of clusters and their influence on employment growth. The analysis is based on the theoretical framework of the cluster development and experiences in some old and new EU countries. The research shows that clusters in EU 27 and Croatia differ in many dimensions: the point they arise, the type of products and services they produce, their stage of development, and the business environment that surrounds them. The analysis of European regional clusters shows that most of European clusters are rather young. A large majority of them were created after 1970 and the development of regional clusters in Croatia begun even later. Namely, expansion of Croatian regional clusters mainly started after year 2005. The innovative activity of European clusters is relatively concentrated in few areas in Europe (West Germany and most regions of Austria, the North and East of France, the South-east part of United Kingdom, the Netherlands and in some Scandinavian countries, mostly in Sweden). Our research selected the most dominated clusters in EU-27 and Croatia: the agricultural products cluster, the construction cluster, the IT cluster, the tourism and hospitality cluster and the transportation and logistics cluster. The investigation confirms that in the agricultural products cluster the highest number of employees has the region of the Mediterranean Spain, and in the construction cluster, the IT cluster, the tourism and hospitality cluster and the transportation and logistics cluster has Italy. Majority of clusters in Croatia function in manufacturing and agriculture sector, have more than 500 employees (40% of all), mainly are financed by membership (68%), and produce for Croatian market (72%).
Keywords: 330